Fatty acid metabolization and insulin regulation prevent liver injury from lipid accumulation in Himalayan marmots - Ziqiang Bao; Cheng Guo; Yi Chen; Cheng Li; Tao Lei; Shuailing Zhou; Dunwu Qi; Zuofu Xiang (Cell Reports, 2023)
Summary: Fat storage and weight gain are dominant traits for hibernating mammals. However, excessive fat accumulation may cause liver damage. Here, we explore the lipid accumulation and metabolic processes of the Himalayan marmot (Marmota himalayana), a hibernating rodent species. We find that the unsaturated fatty acid (UFA) content in food was consistent with a large increase in the body mass of Himalayan marmots. Metagenomic analysis shows that Firmicutes Bacterium CAG:110 plays a synergistic role by synthesizing UFAs, which is demonstrated by fecal transplantation experiments, indicating that the gut microbiome promotes fat storage in Himalayan marmots for hibernation. Microscopic examination results indicate that the risk of fatty liver appears at maximum weight; however, liver function is not affected. Upregulations of UFA catabolism and insulin-like growth factor binding protein genes provide an entry point for avoiding liver injury.